A pesquisa em televisão digital no Brasil: apontamento sobre o levantamento bibliográfico realizado de 1995-2008 sobre o assunto - Xavier, Renan [UNESP]; Carvalho, Juliano Maurício de [UNESP]; Ikeda, Patrícia Benetti [UNESP]; Cleto, Gabriela Estefano Reis [UNESP] (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2010)
In Brazil, the discussion about thereplacement of analog television signals to digitaland its impact on society, in media companies andgovernment began in the 90s. Embryonic steps towardsdigitalisation of the television signal ground were thegovernment of Fernando Collor de Mello (1990-1992),with advances during the government of FernandoHenrique Cardoso (1994-2001) and in the governmentof Luiz Inacio Lula da Silva (2002). The academy startsthe discussion in 1996. This article aims to bring to lightthe results obtained from the survey Digital television:a historical perspective , which received the supportof CNPq for funding of two scholarships for scientifi cinitiation between August 2008 and July 2009. Theproject sought to identify what has been published onthe subject in the fi eld of Social Sciences and from threemacrodescritores (information management, publicpolicy and value chain), providing the li ing of a virtualcollection Zotero bibliographic innovative platform.The mapping serves to show the growing interest anddevelopment of research in the country during theperiod - when the number jumped to three works inthe fi rst seven years (1995-2001) to 198 in the last sevenyears (2002-2008). The research sought to identify themajor authors and works related to digital televisionand published in the country. The survey took intoaccount books, articles published in books, journals,Annals of Compós and Intercom, and dissertations andtheses. Data and refl ections on the survey are containedin this communication.

No Brasil, a discussão sobre a substituição dosinal televisivo analógico pelo digital e seu impacto nasociedade, nas empresas de comunicação e no governoteve início na década de 90. Os passos embrionáriospara a digitalização do sinal televisivo terrestre foramno governo Fernando Collor de Mello (1990-1992), comavanços no governo Fernando Henrique Cardoso (1994-2001) e no governo de Luiz Inácio Lula da Silva (2002).A academia inicia a discussão em 1996. Este artigo tem oobjetivo de trazer à tona os resultados obtidos a partir dapesquisa Televisão digital: uma perspectiva histórica ,que recebeu o apoio do CNPq para fi nanciamento deduas bolsas de Iniciação Científi ca entre agosto de2008 e julho de 2009. O projeto tratou de identifi caro que foi publicado sobre o assunto no campo deCiências Sociais e a partir de três macrodescritores(gestão da informação, políticas públicas e cadeia devalor), disponibilizando o levantamento em um acervovirtual bibliográfi co inovador na plataforma Zotero. Omapeamento deixa em evidência o crescente interessee desenvolvimento da pesquisa na área no país noperíodo quando a quantidade saltou de três obras nosprimeiros sete anos (1995-2001) para 198 nos últimossete anos (2002- 2008). A pesquisa procurou identifi caros principais autores e obras relacionados à televisãodigital e publicadas no país. O levantamento levou emconta livros, artigos publicados em livros, periódicos,anais da Compós e Intercom, além de dissertações eteses. Os dados e refl exões sobre o levantamento estãocontidos nesta comunicação.
Research on digital television in Brazil: notes on the literature review from 1995-2008 on the subject
Keywords: Digital TV; Information management; Communication policies; Value chain bibliography; Televisão digital; Gestão da informação; Políticas de comunicação; Cadeia de valor; Levantamento bibliográfico